2021
DOI: 10.3389/fpsyg.2021.740354
|View full text |Cite
|
Sign up to set email alerts
|

Commercializing Sonic Seasoning in Multisensory Offline Experiential Events and Online Tasting Experiences

Abstract: The term “sonic seasoning” refers to the deliberate pairing of sound/music with taste/flavour in order to enhance, or modify, the multisensory tasting experience. Although the recognition that people experience a multitude of crossmodal correspondences between stimuli in the auditory and chemical senses originally emerged from the psychophysics laboratory, the last decade has seen an explosion of interest in the use and application of sonic seasoning research findings, in a range of multisensory experiential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 124 publications
(200 reference statements)
0
10
0
Order By: Relevance
“…Thereafter, we go on to examine the various ways in which harmony has been introduced in a crossmodal, or multisensory, context. We consider the combination of music and painting (e.g., in the rich literature on the ultimately unsuccessful ideal of “color music”; Plummer, 1915 ; Rimington, 1915 ; Sullivan, 1914 ; Zilczer, 1987 ), music and scent (e.g., in the occasional development of scent organs; see Spence, 2021 , for a review), and the emerging literature on “sonic seasoning” with off-the-shelf, or increasingly bespoke, musical compositions and soundscapes being paired with specific tasting experiences (e.g., see Spence, 2020d , 2022 ; Spence et al, 2021 ). One of the key questions here becomes whether harmony can be experienced crossmodally, or whether instead it is only ever experienced within individual senses.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, we go on to examine the various ways in which harmony has been introduced in a crossmodal, or multisensory, context. We consider the combination of music and painting (e.g., in the rich literature on the ultimately unsuccessful ideal of “color music”; Plummer, 1915 ; Rimington, 1915 ; Sullivan, 1914 ; Zilczer, 1987 ), music and scent (e.g., in the occasional development of scent organs; see Spence, 2021 , for a review), and the emerging literature on “sonic seasoning” with off-the-shelf, or increasingly bespoke, musical compositions and soundscapes being paired with specific tasting experiences (e.g., see Spence, 2020d , 2022 ; Spence et al, 2021 ). One of the key questions here becomes whether harmony can be experienced crossmodally, or whether instead it is only ever experienced within individual senses.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2021) further explored the acoustical/musical attributes that best match saltiness and found that auditory attributes based on emotional associations (negative valence, minor mode, and high arousal), long decay durations, regular rhythm, and a high degree of auditory roughness were associated most strongly with saltiness. These findings on sonic seasoning have been used in marketing-led activations (Spence et al, 2021) and further understanding of how music influences consumers' perceptions of food. Crisinel et al (2012) demonstrated for the first time that individuals evaluate food differently based on the music they hear while tasting it.…”
Section: Introductionmentioning
confidence: 94%
“…It has often been reported that (differences in) verticality provide a striking basis for metaphor in humans (e.g., Cian, 2017;van Rompay et al, 2012. Similarly, the literature on 'sonic seasoning' (referring to the deliberate pairing of sound/music with taste/flavour in order to enhance, or modify, the multisensory tasting experience; Spence et al, 2021) has also demonstrated robust crossmodal correspondences between basic taste and pitch height, with bitter tastes being associated with low notes whereas sweet and sour tastes tend to be associated with higher notes instead (e.g., Knöferle and Spence, 2012;Wang et al, 2015). That said, the spatial (e.g., elevation) association with the basic tastes does not appear to be particularly strong, with documenting only weak evidence to suggest that people associate sweet tastes with higher locations than the other tastes.…”
Section: Orientation Position and Movementmentioning
confidence: 99%